24 x 36 [videorecording (DVD)] : a movie about movie posters - Dante, Joe, 1948-; Hodge, Thomas (Commercial artist) (FilmRise : MVD Visual, 2018)
"Through interviews with a number of key art personalities from the '70s and '80s, as well as many modern, alternative poster artists -- 24x36 aims to answer the questions -- What happened to the illustrated movie poster? Where did it disappear to and why? In the mid 2000s, filling the void left behind by Hollywood's abandonment of illustrated movie posters, independent artists and galleries began selling limited edition screenprinted posters. This movement has quickly exploded into a multi-million dollar industry, with prints selling out online in seconds, inspiring Hollywood studios to take notice of illustration in movie posters once more."--Container.